Investigations of a new EPS-insulated mortar-free reusable interlocking block for sustainable buildings - Hui Gao; Moses Mwenda Karani; Li Zuo; Zhongwei Zhao (PLoS ONE, 2026)
Sustainable, energy-efficient, and reusable construction systems have increasingly been demanded due to the increasing amount of plastics, waste, demolition debris, and the carbon footprints associated with existing traditional materials used in the construction industry. In contribution to this, this study innovates a new enveloped insulated interlocking concrete block (IICB) made of recycled aggregate concrete (RAC) and expanded polystyrene (EPS), which can be shortened to EIICB. This innovation aims to maximize the potential of producing thermally insulated blocks at full scale, focusing on features such as portability, dry assembly, speedy execution, reusability, inventiveness, high compression, low absorption, and sustainability, which cannot be fully achieved by previous concrete blocks. Compared with conventional concrete blocks, the EIICB reduces concrete material usage and achieves an estimated 73.5% reduction in CO₂ emissions. Experimental evaluation showed an average compressive strength of 7.91 MPa, water absorption of 4.74%, and a calculated thermal R-value of 15.05, demonstrating improved thermal efficiency and compliance with structural requirements for non-load-bearing and light structural applications. This work has provided key benefits: transforming waste concrete into valuable materials for affordable and sustainable construction, providing energy-efficient solutions for modern construction, protecting the environment, and aligning with sustainable building practices. The results from this study show the EIICB’s ability to promote the construction of low-cost, energy-efficient housing and indicate future opportunities for optimization, full-scale thermal validation, and life-cycle performance assessment.